2015
DOI: 10.1177/0890334415585078
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of Milk of Healthy and Mastitis-Suffering Women

Abstract: Human milk contains a complex microbial metagenome constituted by the genomes of bacteria, archaea, viruses, fungi, and protozoa. In mastitis cases, the milk microbiome reflects a loss of bacterial diversity and a high increase of the sequences related to the presumptive etiological agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
262
2
19

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(300 citation statements)
references
References 64 publications
17
262
2
19
Order By: Relevance
“…In 2015, Jimenez et al, (33) reported shotgun sequencing of 10 healthy and 10 mastitic breast milk samples, which revealed that microbial abundance in mastitis-infected mother was higher than that of the healthy lactating mother. Thus, based on culture-dependent and independent studies, it can be concluded that an infected mother has high abundance of bacteria resulting in high CFU/mL and the amount of somatic cell is also higher as a result of an action by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, Jimenez et al, (33) reported shotgun sequencing of 10 healthy and 10 mastitic breast milk samples, which revealed that microbial abundance in mastitis-infected mother was higher than that of the healthy lactating mother. Thus, based on culture-dependent and independent studies, it can be concluded that an infected mother has high abundance of bacteria resulting in high CFU/mL and the amount of somatic cell is also higher as a result of an action by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Острый мастит Золотистый стафилококк (S. аureus) является основным этиологическим агентом острого мастита [9][10][11]. Попадая в молочную железу, он может размножаться и выделять токсины, которые приводят к сильному воспалению ткани молочных желез, и, как следствие, при этом обычно появ-ляются выраженные местные симптомы: покраснение груди, высокая температура, боль (рис.…”
Section: этиопатогенез лактационного маститаunclassified
“…К сожалению, точные причинно-следственные связи, при-ведшие к переходу от колонизации до инфекции, еще плохо определены в исследованиях in vivo. Состав микро-биома молока зависит от организма хозяина [11,20]. Этот состав может стать важным фактором, который определяет, будет ли женщина страдать, или же будет защищена от мастита.…”
Section: микробные факторыunclassified
“…Мікроорганізми порожнини конкурують із потенційно небезпечними транзиторними мікроорганізмами, які випадково потрапляють із зовнішнього середовища, формують у порожнині кишки біологічні умови, що сприяють підтримці оптимальної концентрації таксонів фізіологічної нормофлори, беруть участь у процесах метаболізму, біосинтезу, дезінтоксикації тощо [4,5]. Тому вивчення етіологічної структури кишкових інфекцій, що зумовлені умовно патогенними мікроорганізмами, а також встановлення змін популяційного рівня мікробіоти порожнини товстої кишки в дітей грудного віку, які хворі на гостру кишкову інфекцію, за природного вигодовування визначає актуальність наукової праці [6,7].…”
Section: оригинальные исследованияunclassified